Stochastic control of freeway corridor systems - Athans, M.; Houpt, P. K.; Looze, D.; Orlhac, D.; Gershwin, S. B.; Speyer, J. L. (1975 IEEE Conference on Decision and Control including the 14th Symposium on Adaptive Processes, 1975)
This paper deals with the dynamic stochastic control of a freeway corridor system, which consists of a multilane freeway interconnected with entry and exit ramps to one or more parallel traffic arterials, and subject to ramp controls and signals at intersections. Key issues associated with the use of modern estimation and control theory are presented.